2014
DOI: 10.1371/journal.pone.0087698
|View full text |Cite
|
Sign up to set email alerts
|

The Lin28/Let-7 System in Early Human Embryonic Tissue and Ectopic Pregnancy

Abstract: Our objective was to determine the expression of the elements of the Lin28/Let-7 system, and related microRNAs (miRNAs), in early stages of human placentation and ectopic pregnancy, as a means to assess the potential role of this molecular hub in the pathogenesis of ectopic gestation. Seventeen patients suffering from tubal ectopic pregnancy (cases) and forty-three women with normal on-going gestation that desired voluntary termination of pregnancy (VTOP; controls) were recruited for the study. Embryonic tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The present study was approved by the Institutional Review Board/Independent Ethics Committee of the Hospital Universitario La Fe, Valencia, Spain. Early embryonic tissue (mostly trophoblast) was collected after obtaining the corresponding informed consent from each patient, as described elsewhere (28,29).…”
Section: Ethical Approvalmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study was approved by the Institutional Review Board/Independent Ethics Committee of the Hospital Universitario La Fe, Valencia, Spain. Early embryonic tissue (mostly trophoblast) was collected after obtaining the corresponding informed consent from each patient, as described elsewhere (28,29).…”
Section: Ethical Approvalmentioning
confidence: 99%
“…A total of 108 women with a normal ongoing pregnancy that desired a voluntary termination of pregnancy (VTOP) and 45 patients suffering from tubal ectopic pregnancy were recruited, following previous described criteria (28,29). All individuals (EP and VTOP) included in this study signed an informed consent, and samples were properly dated according to the last menstrual period (week of pregnancy).…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In consequence, the small sample size in our study and other studies may be the reason for the discrepancy regarding circulating levels of cell-free miR-323-3p among the studies (4,21). A larger study is necessary to determine whether cell-free miR-323-3p is a universal biomarker for the identification of EP (4).…”
Section: Figurementioning
confidence: 69%
“…Furthermore, Lozoya et al (21) reported that the expression of miR-323-3p is lower in EP tissues than in normal human embryonic tissues at 7 to 9 weeks of gestation. Our…”
Section: Discussionmentioning
confidence: 99%